Evaluasi Penyusunan Anggaran Organisasi Perangkat Daerah Dinas Kesehatan Kabupaten Pamekasan - Anna Atika Maghfiroh; Agus Sugiono (Jurnal Simki Economic, 2022)
The purpose of this study was to evaluate the preparation of the regional apparatus organization budget for the Dinas Kesehatan Kabupaten Pamekasan. This research is a qualitative research. Sources of data in the form of primary data obtained from observations and interviews with resource persons from the Dinas Kesehatan Kabupaten Pamekasan and secondary data in the form of administrative document studies.The results showed that the process of preparing the budget planning at the Dinas Kesehatan Kabupaten Pamekasan started from the proposal for the Puskesmas which was combined with the results of the MP-3 then combined with the proposals of various Sections and Sub-Sections to be submitted to the MP-3 at the Pamekasan Regency level. The goals of the health program at the Dinas Kesehatan Kabupaten Pamekasan refer to the Draft Strategic Plan which contains the Vision, Mission, goals and objectives of the health program in 11 policy packages that serve as barometers for health development. The RASK proposal and the realization of the budget are RASK proposals that are in accordance with the priority scale in order to obtain an effective and efficient budget and it is necessary to advocate for policy makers, especially to Bapeda and TPA Legislative. The preparation of planning, determination and realization of the budget experienced problems in the quality and quantity of human resources at the Dinas Kesehatan Kabupaten Pamekasan.